2012
DOI: 10.4236/psych.2012.32029
|View full text |Cite
|
Sign up to set email alerts
|

Psychology Students’ Beliefs about Integrating Complementary and Alternative Therapy (CAT) into Their Future Psychology Practice

Abstract: We investigated whether belief-based differences exist between students who have strong and weak intentions to integrate complementary and alternative therapy (CAT) into future psychology practice by recommending CAT or specific CAT practitioners to clients. A cross-sectional methodology was used. Psychology undergraduate students (N = 106) participated in a paper-based questionnaire design to explore their underlying beliefs related to CAT integration. The study was undertaken at a major university in Queensl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In some countries (e.g., America and England) specific CM approaches are accepted by psychologists and integrated into their practice, such as meditation and mindfulness; yet they were not previously considered a component of psychology [ 31 , 33 , 34 ]. Some psychologists report engaging with CM based on holistic and client centred principles [ 3 , 35 , 36 ], while others discuss client demand and acknowledge the cultural relevance of some CM (Barimah and Akotia 2015 [ 18 , 37 39 ]. Psychologists are also seeking training in, and already using, some CM approaches in their practice [ 1 , 3 , 4 , 19 ].…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some countries (e.g., America and England) specific CM approaches are accepted by psychologists and integrated into their practice, such as meditation and mindfulness; yet they were not previously considered a component of psychology [ 31 , 33 , 34 ]. Some psychologists report engaging with CM based on holistic and client centred principles [ 3 , 35 , 36 ], while others discuss client demand and acknowledge the cultural relevance of some CM (Barimah and Akotia 2015 [ 18 , 37 39 ]. Psychologists are also seeking training in, and already using, some CM approaches in their practice [ 1 , 3 , 4 , 19 ].…”
Section: Key Pointsmentioning
confidence: 99%
“…Australian psychologists note the absence of CM relevant guidelines [ 1 , 48 ]. The concern for lack of guidelines is reported by participant psychologists in relevant papers, and includes: 1) confusion around the ethical responsibility to advise clients appropriately about CM [ 5 , 49 ], 2) what is allowable in terms of integrating CM in clinical practice [ 19 , 36 ], 3) how the efficacy of CM can be explored by psychologists in safe and ethical ways [ 4 , 35 ], and 4) that psychologists in clinical practice are attempting to address consumer demand for CM without clear policy and guidelines [ 2 , 3 , 47 ]. Australian studies also cite lack of knowledge or education as a barrier to psychologist engagement with CM [ 43 , 50 ].…”
Section: Key Pointsmentioning
confidence: 99%
“…Higher total scores reflect stronger beliefs in CAM as being advantageous or beneficial. Previous studies have found these four items to be valid and psychometrically sound in measuring behavioural beliefs relating to CAM (Wilson & White, 2007;Wilson & White, 2008;Wilson, Hamilton, & White, 2012). Data was analysed using SPSS-19 (Corp, 2010).…”
Section: Insert Tablementioning
confidence: 99%